2016
DOI: 10.1016/j.pjnns.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral vasomotor reactivity in neurodegenerative diseases

Abstract: Small-caliber cerebral vessels change their diameters in response to alterations of key metabolite concentrations such as carbon dioxide or oxygen. This phenomenon, termed the cerebral vasomotor reactivity (CVMR), is the basis for blood flow regulation in the brain in accordance with its metabolic status. Typically, CVMR is determined as the amount of change in cerebral blood flow in response to a vasodilating stimulus, which can be measured by various neuroimaging methods or by transcranial Doppler. It has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 85 publications
0
23
0
Order By: Relevance
“…First, the BHI was obtained by calculating the percentage change from MFV during baseline and the maximal increase in flow velocity at the end of the breath hold. This percentage change was divided by 30 seconds (or the actual time subjects held their breath) . Second, BHAI and CVR were calculated by linear regression of the most linear portion of the MFV change during the breath‐hold maneuver …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the BHI was obtained by calculating the percentage change from MFV during baseline and the maximal increase in flow velocity at the end of the breath hold. This percentage change was divided by 30 seconds (or the actual time subjects held their breath) . Second, BHAI and CVR were calculated by linear regression of the most linear portion of the MFV change during the breath‐hold maneuver …”
Section: Methodsmentioning
confidence: 99%
“…Then, PI for each cardiac cycle was calculated by subtracting diastolic velocity ( Vd ) from the systolic velocity ( Vs ), and then dividing by the MFV . Finally, CVR was calculated using both BHI and BHAI indices …”
Section: Methodsmentioning
confidence: 99%
“…(Koudriavtseva et al 2015) Many vasodilators and constrictors derived from the endothelium, neuronal innervation and glial cells are involved in CBF regulation. (Koudriavtseva et al 2015;Smolinski and Czlonkowska 2016) Also blood pressure plays an important role in brain perfusion control. (Smolinski and Czlonkowska 2016) Furthermore, vascular changes can occur in physiological conditions due to aging.…”
Section: Introductionmentioning
confidence: 99%
“…(Koudriavtseva et al 2015;Smolinski and Czlonkowska 2016) Also blood pressure plays an important role in brain perfusion control. (Smolinski and Czlonkowska 2016) Furthermore, vascular changes can occur in physiological conditions due to aging. (Liu et al 2012;Tsvetanov et al 2015) Correlations between age and CBF have been previously observed in MS patients, (Amann et al 2012) but no studies have investigated the relationship between age and CVR in MS.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Moreover, in Alzheimer's disease, reduced CVR has been demonstrated with many techniques, including BOLD, ASL and TCD. 25 Marshall et al hypothesized that CVR might be reduced in MS due to habituation of cerebral vasculature to chronically increased nitric oxide concentrations. 18 However, nitric oxide seems essential for hypercapnia-induced cerebral vasodilation, 26 and consequently for CVR, and we were not able to find any previous evidence that nitric oxide, when chronically increased, like in MS, 27 has an opposing effect.…”
mentioning
confidence: 99%